Isso não é África, é Cabo Verde: o movimento claridoso e a busca por uma identidade crioula (1931-1960) - Taciana Almeida Garrido de Resende (2014)
This Masters thesis intends to discuss and evaluate the different political-identitarian discourses by four intellectuals who contributed with the Cape Verdean magazine Claridade: an arts and belles lettres publication from the period comprehended between the decades of 1930 and 1950. The pluralism of the productivity of Baltasar Lopes, João Lopes, Henrique Teixeira de Sousa and Gabriel Mariano in numerous press vehicles in the archipelago will be analyzed with the intent of verifying, between these authors, different or similar views concerning the Cape Verdean society - which united or dispersed them as a group, namely the claridosos. Combined with the specialized bibliography, the validity of the analysis in terms of generation (in strictly chronologic meaning) will be discussed, since Claridade, in its twenty-four years of existence, embodied young and old literati from the archipelagos intellectual scene.